Quo Vadis? A study of the state and development of coaching in Portugal - Fontes, A.; Dello Russo, S. (International Journal of Training and Development, 2019)
Although coaching programs are becoming increasingly widespread across the world, in some countries this practice has only been introduced in recent years. To better understand the coaching context in one such country, Portugal, and to identify future trends and directions, a survey was carried out among 255 coaches via social media, using the snowball approach. We aimed to uncover the predominant background of coaches and whether this is associated with features of their practice, most notably their theoretical positions and the use of any tools or instruments. We also explored aspects related to the coachees’ most recurrent needs for coaching, and the positive and negative effects that coaches observe more frequently. The results of this descriptive study reveal, among other things, that there is room for more theory-driven methodologies that can be replicated and standardized and, therefore, ultimately contribute to coaching professionalization.